The effects of an exercise program on the response of CD4+ and CD8+ T lymphocytes in people living with HIV/AIDS (PLWHA): a systematic review - Balieiro Capela, Ilva Lana; Santiago de Oliveira, Luciana; Pinto de Lima Ribeiro, Andressa Karoline; Rosário Vallinoto, Antonio Carlos; Vieira Cayres Vallinoto, Izaura Maria (Revista de Patologia Tropical / Journal of Tropical Pathology, 2023)
People living with HIV and AIDS (PLWHA) have decreased functional capacity, muscle strength and quality of life. Furthermore, HIV/AIDS can cause some adverse effects and long-term problems, such as sarcopenia and some peripheral neuropathies. A common practice among the healthy population that helps to modify these risk factors is to practice of some kind of exercise, such as aerobic and resistance exercises. The objective of this review is to assess the possible effects of exercise on the increase in CD4+ and/or CD8+ T lymphocytes among PLWHA. The LILACS, IBECS, PubMed/MEDLINE, Cochrane Library, SciELO, PEDro, ScienceDirect and Bireme databases were systematically searched for randomized controlled trials. The following descriptors were used in the search in English, Portuguese and Spanish: HIV, physical functional performance, resistance training, and aerobic exercise. The methodological quality of the studies was evaluated using the PEDro scale. The data were read, analyzed, extracted, and synthesized. Of the 3,319 studies consulted, only five met the inclusion criteria. A synthesis of the five selected studies was performed, all of which were randomized controlled trials. It was concluded that aerobic and/or resistance exercise protocols have a positive effect on immunity (CD4+ and/or CD8+ T lymphocytes and TNF-α) and on the metabolic/ biochemical profile of PLWHA. KEY WORDS: HIV; AIDS; CD4; CD8; exercise.